2021
DOI: 10.1007/s12665-021-09743-y
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical indicators of the influence of a lined municipal landfill on groundwater quality: a case study from Poland

Abstract: The paper aims to determine the most significant physicochemical indicators of the effects that a lined landfill in southern Poland has had on groundwater quality. The results of the tests of groundwater and leachate water from the landfill for the period 2009 to 2016 were subjected to a detailed statistical analysis based on the 10 physicochemical parameters. A factor analysis was conducted considering the European Union and national requirements for landfills using analytical and statistical tools. The leach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Exchangeable Ca showed negative signifcant correlations with Cl − , NO 3 − , and HCO 3 − (Table 6). Generally, the correlation coefcient results between the selected soil chemical properties were similar to the reported correlations between similar soil properties in literature [72][73][74]. Correlation results, and a close view of other soil chemical parameters in this study, indicated that the possible main soil salt anions in Abaya and Chamo Lakes were Cl − and HCO 3 − .…”
Section: Salt-afected Soils Correlation Between Selectedsupporting
confidence: 89%
“…Exchangeable Ca showed negative signifcant correlations with Cl − , NO 3 − , and HCO 3 − (Table 6). Generally, the correlation coefcient results between the selected soil chemical properties were similar to the reported correlations between similar soil properties in literature [72][73][74]. Correlation results, and a close view of other soil chemical parameters in this study, indicated that the possible main soil salt anions in Abaya and Chamo Lakes were Cl − and HCO 3 − .…”
Section: Salt-afected Soils Correlation Between Selectedsupporting
confidence: 89%
“…Mostly, the groundwater variables of factor F1 revealed the genesis of the geogenic source. However, pH, EC, and TDS resulted from mineral dissolution, the leakage of aquifer compositions, and saline bases [ 72 , 73 , 74 ], whereas Ca 2+ , Na 2+ , HCO 3 – , and SO 4 2− originated from geogenic sources, i.e., ion exchange processes, rock weathering, water-rock interaction, and dissolution of albite muscovite, and dolomite minerals. The potential sources contributing to Ca 2+ , Na 2+ , and SO 4 2− were attributed to be calcite (CaCO₃), plagioclase (NaAlSi 3 O 8 –CaAl 2 Si 2 O 8 ), and sulfate bearing minerals such as gypsum polyhalite (K 2 Ca 2 Mg (SO 4 ) 6 , (CaSO 4 ·2H 2 O).…”
Section: Resultsmentioning
confidence: 99%
“…The electrical conductivity value ranged from 305-5570 µs/cm, with a mean value of 1200 µs/cm, in all groundwater sources of district Sanghar. The high (EC) water samples reflect leakage or suspension of the aquifer constituents or other bases such as saline water bodies [45]. The pH of samples was in the range of 6.8 to 8.7, having a mean value of 7.6, showing the alkaline nature of groundwater sources.…”
Section: Groundwater Compositionmentioning
confidence: 99%